The Implementation of Religious Moderation in the Merdeka Curriculum: A Case Study of Madrasahs in Binjai City - Hadinata, Arie Bastian; Harahap, Surya Bakti; Deni, Indira Fatra; Bagaskara, Muhammad Katon (Universitas Islam Lamongan, 2025)
This study aims to analyze the implementation of religious moderation values within the Merdeka Curriculum in madrasahs in Binjai City, identify supporting and inhibiting factors in their application, and evaluate the effectiveness of the teaching strategies used to integrate these values. This research employed a qualitative case study approach, using data collected through in-depth interviews, participatory observations, and document analysis. The research subjects consisted of madrasah principals, Islamic Religious Education teachers, and students at three madrasahs in Binjai City that have implemented the Merdeka Curriculum. The findings reveal that religious moderation values have been integrated into the curriculum and learning processes through various strategies, including contextual and collaborative approaches and the use of digital media. Supporting factors include teacher commitment and madrasah policies, while inhibiting factors involve limited time, teacher capacity, and inadequate evaluation tools. The effectiveness of teaching strategies needs further enhancement through teacher training, development of teaching materials, and comprehensive evaluation to ensure the internalization of religious moderation within madrasah culture. This study offers recommendations for policymakers to strengthen the implementation of religious moderation in Islamic education in Indonesia.